Comparative genomic analysis uncovered phylogenetic diversity, evolution of virulence factors, and horizontal gene transfer events in tomato bacterial spot Xanthomonas euvesicatoria - Huang, Chien-Jui; Wu, Ting-Li; Wu, Yu-Lin; Wang, Ruei-Shiuan; Lin, Yao-Cheng (Frontiers in Microbiology, 2024)
Bacterial spot poses a significant threat to global pepper and tomato production. The causal xanthomonads are highly diverse and are classified into four lineages within three species, including Xanthomonas euvesicatoria pv. euvesicatoria (Xee), X. euvesicatoria pv. perforans (Xep), X. hortorum pv. gardneri, and X. vesicatoria. In addition to typical Xep strains, tomato bacterial spot xanthomonad strains that are phylogenetically related to an atypical Xep strain NI1 from Nigeria was found in Taiwan, based on gapA gene comparison.This study aimed to investigate the genetic structure of Taiwanese Xep strains and determine the phylogenetic position of these atypical strains using comparative genomic analyses. We completed high-quality, gap-free, circularized genomes of seven Taiwanese Xep strains and compared them with those of X. euvesicatoria pathovars. Average nucleotide identity, core genome analysis, and phylogenomic analysis revealed that three sequenced strains were typical Xep, whereas the other four clustered with the atypical strain NI1, forming a distinct genomovar within X. euvesicatoria, which we propose to name X. euvesicatoria genomovar taiwanensis (Xet). This new lineage likely originated in Taiwan and has since spread to Nigeria through global seed trade. At the genomovar level, the chromosomes remained conserved among the Taiwanese strains, whereas the plasmids likely contributed to bacterial virulence, avirulence, and field fitness. Gap-free genomes have revealed important associations between the evolution of type III effectors, horizontal gene transfer events, plasmid diversity, and recombination. This study highlights the critical roles of horizontal gene transfer and plasmids in shaping the genetic makeup, evolution, and environmental adaptation of plant pathogenic xanthomonads.